Incomes of the population of the Republic of Kazakhstan as the main criterion for assessing its standard of living - Kapezova, A.E.; Bakirbekova, A.M. (Economic series of the Bulletin of L.N. Gumilyov ENU, 2023)
In this article, the income of the population of the Republic of Kazakhstan is based on its assessment of the standard of living and explains what kind of income is important for the population in the income structure of the population. It is also stated that a change in the structure of the population’s monetary income may be one of the factors that may contribute to the strengthening or differentiation of the population’s income.